A “Just Hearing”: Reading Shyam Selvadurai’s The Hungry Ghosts as Counter to State Practice - Rodrigo, Arun Nedra (Studies in Canadian Literature, 2015)
The immigration form that refugees are expected to complete within fifteen days of arriving on Canadian soil requests that refugees provide a personal narrative history. This request appears to extend an articulation of selfhood, and welcome the refugee into the fold of humanity. However, the reality is that these forms serve the self-endorsing practices of the state in its maintenance of sovereignty both juridically, in the ordering of the narrative process, and culturally, through the reification of the European, Christian traditions of the settler cultures of Canada, thereby reinstating the refugee as a minoritized subject. This essay examines the narrative demands made by the Personal Information Form (PIF) on Tamil refugees who arrived in Canada at the height of the civil conflict, and turns to a reading of Shyam Selvadurai’s The Hungry Ghosts to explore ways in which the novel may serve as a critical intervention in the refugee hearing process, allowing the refugee to document and make truth claims in her own history of trauma, giving her experience more complex meaning. Building upon Paul Gready’s claim that the “unique truth practices and repertoire available to the novel as a genre” allow readers to explore “uncomfortable truths” in matters pertaining to human rights conflicts, this essay argues that in some instances the novel provides a more “just hearing” for the refugee.